STUDI TENTANG POTENSI MOBILE-ASSISTED LANGUAGE LEARNING DALAM PEMBELAJARAN BAHASA PRANCIS UNTUK MAHASISWA BARU DI UNIMED - Hadijah Handayani Sibuea; Riza Harani Bangun (Smart Education, 2025)
Abstract: French language learning for first-year students at Universitas Negeri Medan (UNIMED) still faces several challenges, particularly related to the limitations of conventional teaching methods that lack flexibility and integration with technological developments. Along with the rapid advancement of information and communication technology, Mobile-Assisted Language Learning (MALL) has emerged as an innovative approach with the potential to enhance the quality of foreign language learning. This study aims to examine the potential, benefits, and challenges of using MALL in French language learning for first-year students at UNIMED. A descriptive qualitative approach was employed, involving first-year French language education students and French language lecturers as research participants. Data were collected through in-depth interviews, questionnaires, observations, and document analysis, and analyzed using thematic analysis and descriptive statistics. The findings indicate that the use of MALL increases students’ motivation, confidence, and French language proficiency, particularly in speaking and listening skills, with an average improvement of 15%. However, several challenges were also identified, including limited internet access, the dominance of English as the instructional language in some applications, and insufficient integration between mobile learning and face-to-face instruction. Therefore, more structured integration strategies and lecturer training are required to optimize the implementation of MALL in French language learning at UNIMED.Keywords: Mobile-Assisted Language Learning, MALL, French language learning, educational technology, first-year students.Abstrak: Pembelajaran bahasa Prancis bagi mahasiswa baru di Universitas Negeri Medan (UNIMED) masih menghadapi berbagai tantangan, terutama terkait keterbatasan metode pembelajaran konvensional yang kurang fleksibel dan kurang terintegrasi dengan perkembangan teknologi. Seiring pesatnya perkembangan teknologi informasi, Mobile-Assisted Language Learning (MALL) hadir sebagai alternatif inovatif yang berpotensi meningkatkan kualitas pembelajaran bahasa asing. Penelitian ini bertujuan untuk mengkaji potensi, manfaat, dan tantangan penggunaan MALL dalam pembelajaran bahasa Prancis bagi mahasiswa baru di UNIMED. Penelitian menggunakan pendekatan deskriptif-kualitatif dengan subjek mahasiswa baru dan dosen pengajar bahasa Prancis. Data dikumpulkan melalui wawancara mendalam, kuesioner, observasi, dan studi dokumentasi, kemudian dianalisis menggunakan analisis tematik dan statistik deskriptif. Hasil penelitian menunjukkan bahwa penggunaan MALL mampu meningkatkan motivasi, kepercayaan diri, serta keterampilan berbahasa Prancis mahasiswa, khususnya pada aspek berbicara dan mendengarkan, dengan peningkatan rata-rata kemampuan sebesar 15%. Namun demikian, penelitian ini juga menemukan sejumlah kendala, seperti keterbatasan akses internet, ketergantungan bahasa Inggris pada aplikasi, serta kurangnya integrasi MALL dengan pembelajaran tatap muka. Oleh karena itu, diperlukan strategi integrasi yang lebih terstruktur serta pelatihan bagi dosen agar pemanfaatan MALL dapat dioptimalkan dalam pembelajaran bahasa Prancis di UNIMED.Kata kunci: Mobile-Assisted Language Learning, MALL, pembelajaran bahasa Prancis, teknologi pembelajaran, mahasiswa baru.